An analytical approach to error detection and correction for onboard nanosatellites - Md. Motaharul Islam; Mahmudul Hasan; Zaheed Ahmed Bhuiyan (EURASIP Journal on Wireless Communications and Networking, 2023)
Abstract Nanosatellites are persistently progressing and creating global communication and data transmission. It builds up a colossal request for more progressed and dependable frameworks to transmit faster and more reliable information. A syntactic machine learning approach has been distinguished as a good plot for anticipating single-bit and multiple-bit errors that influence onboard nanosatellites. In this paper, we have proposed an analytical approach to error detection and correction for onboard nanosatellites. We have planned the framework separately with three distinct parts: encoding, error checking, and decoding. It has created an amid information exchange from satellite to the ground station. It has analyzed six camera pictures simultaneously with the assistance of field programmable gate array and EDAC strategies. We have presented the progressed turbo mechanics EDAC for unprecedented transfer speeds of satellite communication and execution & examination with the AWGN and Rayleigh channels to extend the proficiency. EDAC strategies codes have been implemented in MATLAB. This method is straightforward and accomplishes unwavering quality and exactness compared to comparable strategies.